The impact of employee turnover on operational efficiency, innovation, and customer satisfaction: the mediation role of tacit knowledge loss - Sugianto; Firdaus, Rahmad; Suhardi; Amin, Mat (International Journal of Enterprise Modelling, 2025)
This study examines the impact of tacit knowledge loss due to employee turnover on operational efficiency, innovation capability, and customer satisfaction by examining the mediating role of tacit knowledge loss and the mitigating effect of knowledge transfer effectiveness. Using an explanatory quantitative approach, we collected data through closed-ended questionnaires and secondary data from 200 respondents in the manufacturing, service, and MSME sectors in Bangka Belitung. The Structural Equation Modeling (SEM) analysis results revealed that employee turnover significantly increases tacit knowledge loss, which is detrimental to operational efficiency, innovation, and customer satisfaction. This study also highlights that effective knowledge transfer, especially through structured mentoring programs, reduces the impact of tacit knowledge loss. These findings strengthen the resource-based view and knowledge management theory. In addition, our study shows that integrating CRM technology reduces the impact of tacit knowledge loss on customer satisfaction—a previously unexplored factor. Practical implications include recommendations for HR policies that focus on knowledge retention, collaborative training, and technology adaptation for organizations in the digital era. These findings emphasize the importance of a holistic approach that combines social interactions, knowledge management systems, and local cultural contexts to minimize the risk of brain drain.